The orientalist legacy in Huntington’s clash of civilisations theory and Its de-mythization - Mohad, Mawloud; Akhmetova, Elmira (IIUM Press, 2020)
This paper investigates Samuel Huntington’s approach towards the nature of civilisation and its origins, as well as the Orientalist elements within the theory of Clash of Civilisations in particular and Huntington’s thoughts in general. For this purpose, the paper first reviews the theory’s historical background and theoretical basis. Then, it identifies and categorises the nature of the civilisational clash narrative and suggests that it has been used in academic literature since the beginning of the 20th century. This paper also attempts to describe and analyse Huntington’s paradigm and the Orientalist influence on his thought, particularly his idea that the future of the post-Cold War world would be dominated by civilisational conflicts triggered in the fault lines between the seven or eight major world civilisations. In addition, the paper makes an attempt at defragmenting the civilisational clash theory and gives an alternative paradigm. It concludes that the concept of the ‘Clash of Civilisations’ does not fit contemporary historical happenings, but could be considered as an attempt of US policy-makers to trigger rivalry to create potential foes. The article uses qualitative research based on historical, political and analytical methods, through which the authors have collected and interpreted data accordingly.